Laktasi Dalam Al-Quran (Analisis Kesehatan dan Tafsir Al-Misbah Karya M.Quraisy Shihab) - Amalia windy istiqomah; Abdul Kholiq Hasan (Jurnal Riset Multidisiplin Edukasi, 2025)
The low success rate in lactation (breastfeeding) problems up to the age of two and the high stunting rate in Indonesia have made the world a spotlight. This has an impact on the poor quality of human resources from the health aspect. It is not balanced with the motivational studies found in the Qur'an, making one of the causes of the lactation process to stop early. This study examines lactation in the Qur'an with a health analysis approach and interpretation of the interpretation of Al-Misbah's interpretation. The main objective of this study is to understand how the Qur'an describes lactation and the health implications it contains, as well as to assess the relevance of such interpretations to contemporary understandings of maternal and infant health.  To facilitate this thesis process, the author uses the maudhu'I method including the analysis of Qur'anic verses related to lactation verses such as surah al-Baqarah verse 233, surah luqman verse 14, and interpretation of Al-Misbah's interpretation. Data were collected through literature studies on Qur'anic literature and commentary, as well as studies of health literature related to lactation.  The results of the study show that the Qur'an provides comprehensive guidance on lactation, including the duration of breastfeeding and the rights of mothers and children in the context of lactation. The Tafsir Al-Misbah provides an in-depth explanation of the context of these verses and highlights the importance of lactation in the aspects of family health and well-being. These findings indicate that the Qur'anic principles on lactation are relevant to modern medical knowledge and support healthy lactation practices.  This research is expected to contribute to a better understanding of the intersection between religious teachings and health sciences and encourage the application of Qur'anic principles in public health practice, especially in the context of lactation.